Initial COVID-19 Transmissibility and Three Gaseous Air Pollutants (NO2, SO2, and CO): A Nationwide Ecological Study in China - Ran, Jinjun; Zhao, Shi; Han, Lefei; Peng, Zhihang; Wang, Maggie H.; Qiu, Yulan; He, Daihai (Frontiers in Medicine, 2020)
In this study, we conducted an ecological study to examine their effects in the early phase of the pandemic (from December 2019 to February 2020) in China. We found that the associations between the average concentrations of NO2, SO2, and CO and the COVID-19 transmissibility are not statistically clear.